2015
DOI: 10.1103/physreve.92.042145
|View full text |Cite
|
Sign up to set email alerts
|

Stability and anomalous entropic elasticity of subisostatic random-bond networks

Abstract: We study the elasticity of thermalized spring networks under an applied bulk strain. The networks considered are sub-isostatic random-bond networks that, in the athermal limit, are known to have vanishing bulk and linear shear moduli at zero bulk strain. Above a bulk strain threshold, however, these networks become rigid, although surprisingly the shear modulus remains zero until a second, higher, strain threshold. We find that thermal fluctuations stabilize all networks below the rigidity transition, resultin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Critical exponents in elastic networks such as those studied here are usually universal for a given network topology. That is, while they can change for different network topologies (e.g., square lattice networks [53], triangular networks [9], and random-bond networks [54] all show different critical exponents when stabilized with temperature), exponents that evolve in a continuous manner such as these have, to our knowledge, not been reported (although we note that the critical exponent of a quantum phase transition has been shown to vary with the properties of the sub-Ohmic reservoir to which the system is coupled [55]). This, therefore, represents an additional control parameter for the behavior of marginal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Critical exponents in elastic networks such as those studied here are usually universal for a given network topology. That is, while they can change for different network topologies (e.g., square lattice networks [53], triangular networks [9], and random-bond networks [54] all show different critical exponents when stabilized with temperature), exponents that evolve in a continuous manner such as these have, to our knowledge, not been reported (although we note that the critical exponent of a quantum phase transition has been shown to vary with the properties of the sub-Ohmic reservoir to which the system is coupled [55]). This, therefore, represents an additional control parameter for the behavior of marginal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous consequences can be derived from this peculiar vibrational spectrum, with regards to, for instance, elastic or transport properties [4][5][6]. Some of these features are shared with lattices close to isostaticity [7][8][9][10][11][12], which may be exploited to develop meta-materials with novel mechanical properties [13,14].While most studies have focused on the zerotemperature consequences of the vibrational spectrum, we here study the impact of thermal fluctuations. Specifically, we consider the harmonic connectivity network obtained from a jammed packing of repulsive, frictionless spheres close to isostaticity, and study its mechanical properties as we heat up the system to a low but finite temperature.Elastic properties of ordered and disordered networks of springs at finite temperatures have been studied previously [15][16][17].…”
mentioning
confidence: 99%
“…Specifically, we consider the harmonic connectivity network obtained from a jammed packing of repulsive, frictionless spheres close to isostaticity, and study its mechanical properties as we heat up the system to a low but finite temperature.Elastic properties of ordered and disordered networks of springs at finite temperatures have been studied previously [15][16][17]. Most recently, motivated by the attractive properties of highly responsive marginal solids for material science and biophysics, spring networks have been studied near the isostatic threshold [10][11][12]18]. These studies revealed, amongst others, interesting anomalies in the entropic elasticity.…”
mentioning
confidence: 99%
See 2 more Smart Citations